Household specialization and competition for promotion - Spencer Bastani; Lisa Dickmanns; Thomas Giebe; Oliver Gürtler (Review of Economics of the Household, 2024)
We study how the presence of promotion competition in the labor market affects household specialization patterns. By embedding a promotion tournament model in a household setting, we show that specialization can emerge as a consequence of competitive work incentives. This specialization outcome, in which only one spouse invests heavily in his or her career, can be welfare superior to a situation in which both spouses invest equally in their careers. The reason is that household specialization reduces the intensity of competition and provides households with consumption smoothing. The specialization result is obtained in a setting where spouses are equally competitive in the labor market and there is no household production. It is also robust to several modifications of the model, such as varying the number of households, two spouses competing for promotion in the same workplace, and the inclusion of household production.
Keywords: C72; D13; J16; J71; M51; M52; 330; Contest theory; Gender equality; Family; Household; Competition